2023
DOI: 10.3390/biomedicines11020319
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Genomics in Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common chronic condition associated with genetic and environmental factors in which fat abnormally accumulates in the liver. NAFLD is epidemiologically associated with obesity, type 2 diabetes, and dyslipidemia. Environmental factors, such as physical inactivity and an unbalanced diet, interact with genetic factors, such as epigenetic mechanisms and polymorphisms for the genesis and development of the condition. Different genetic polymorphisms seem to be involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Most of the female participants in our study were postmenopausal women, making them susceptible to dietary choline deficiency. Sex, along with variations in lifestyle and nutrient status, can influence gene expression [ 55 ]. The sex-specific analyses performed in our study revealed genetic diversity in the interaction between genetics and nutrition in relation to the risk of NAFLD across individuals with different PEMT rs7946 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the female participants in our study were postmenopausal women, making them susceptible to dietary choline deficiency. Sex, along with variations in lifestyle and nutrient status, can influence gene expression [ 55 ]. The sex-specific analyses performed in our study revealed genetic diversity in the interaction between genetics and nutrition in relation to the risk of NAFLD across individuals with different PEMT rs7946 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is a chronic condition associated with genetic and environmental factors, obesity, type 2 diabetes, and dyslipidemia in which fat abnormally accumulates in the liver. Different genetic polymorphisms seem to be involved in this context [68].…”
Section: Nonalcoholic Fatty Liver Disease Nfldmentioning
confidence: 99%
“…A calorie restriction diet or a low-calorie Mediterranean or vegetarian diet decreased or had no effect on f-SCFAs [ 30 , 31 ], but the effects of dietary fat quality modification on the SCFAs or BCAAs have not been reported yet. Interaction between the GG genotype of PNPLA3 , essential fatty acids and carbohydrates have been reported in NAFLD [ 32 ], but the interaction of PNPLA3 with SCFA and BCAA has not yet been published.…”
Section: Introductionmentioning
confidence: 99%